Expanding the therapeutic horizons of spesolimab: a review of off-label applications for inflammatory skin diseases - Hanlin Zhang; Jia Zhou; Keyun Tang; Xinyi Zhang; Hongzhong Jin (Journal of Dermatological Treatment)
Purpose This review aims to outline the crucial role of IL-36 signaling in inflammatory skin diseases and summarize the therapeutic potential of spesolimab. Our goal is to provide insights into the off-label applications of spesolimab and future directions for its use in treating other challenging skin diseases.Materials and methods We conducted a comprehensive literature search across PubMed, Embase, Web of Science, MEDLINE, Scopus, and the Cochrane Library to identify relevant studies. For RCTs, we additionally searched the ClinicalTrials.gov database.Results In this review, we examine its off-label applications for conditions such as palmoplantar pustulosis, acrodermatitis continua of Hallopeau, hidradenitis suppurativa, pyoderma gangrenosum, and acute generalized exanthematous pustulosis. This review also explores the role of IL-36 in the pathophysiology of these disorders and discusses how spesolimab may address the limitations of current therapies for refractory cases. Randomized controlled trials and case reports are summarized to highlight the efficacy and tolerability of spesolimab across various inflammatory skin conditions. We highlight the challenges presented by the absence of standardized treatment guidelines and the need for larger clinical trials.Conclusions This review underscores the potential of spesolimab to enhance treatment strategies for inflammatory skin diseases.